The Big Naked-backed Bat, Pteronotus gymnonotus, Chiroptera, Mormoopidae, in its northernmost geographic distribution range - Lopez-Wilchis, Ricardo; Méndez-Rodríguez, Aline; Juste, Javier; García-Mudarra, Juan Luís; Salgado-Mejia, Fernando; Guevara-Chumacero, Luis Manuel (THERYA, 2021)
The Big Naked-backed Bat, Pteronotus gymnonotus, is one of the 15 species currently recognized of this genus, with relatively few specimens in scientific collections, besides being poorly studied. It has a geographical distribution spanning from México through Central America and reaching Perú and Brazil, in which it occupies a variety of habitats from desert to tropical forests below 400 meters above sea level. Here, we report the records that demonstrate its presence, and data about its natural history in southeastern México, the northernmost part of its geographic distribution range. Between June 2002 and July 2018, we captured specimens in 44 bat roosts located in southeastern México, including the Parque Estatal Agua Blanca, Macuspana, Tabasco; Grutas de Martínez de la Torre, Matías Romero Avendaño, Oaxaca; and in Cueva de Villa Luz, Tapijulapa, Tabasco. In the three locations mentioned, we recorded the occurrence of P. gymnonotus individuals, whose taxonomic identification at species level was corroborated by both morphological data and genetic analyses. Previously, the only records of P. gymnonotus in México were from only four specimens scattered across time, so these new recorded locations confirm the presence of this species in the country. In addition to this, in Agua Blanca State Park and Villa Luz Cave we found a reproductive resident population. The record from Grutas de Martínez de la Torre is located in the middle of the Tehuantepec Isthmus, a well known biogeographical barrier for many taxa in the transitional area to the Pacific lowlandâ€™s region. We suggest that the occurrence of P. gymnonotus in México is also associated with large remnants of evergreen and gallery forests, located in the lowland areas along the Gulf of México and in the north and east of the Tehuantepec Isthmus.